2017
DOI: 10.1038/s41598-017-03544-9
|View full text |Cite
|
Sign up to set email alerts
|

An Alcaligenes strain emulates Bacillus thuringiensis producing a binary protein that kills corn rootworm through a mechanism similar to Cry34Ab1/Cry35Ab1

Abstract: Crops expressing Bacillus thuringiensis (Bt)-derived insecticidal protein genes have been commercially available for over 15 years and are providing significant value to growers. However, there remains the need for alternative insecticidal actives due to emerging insect resistance to certain Bt proteins. A screen of bacterial strains led to the discovery of a two-component insecticidal protein named AfIP-1A/1B from an Alcaligenes faecalis strain. This protein shows selectivity against coleopteran insects inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…Although the root node‐injury score is not as low as for corn producing Cry34Ab1/Cry35Ab1, PIP‐47Aa holds promise as a new tool to help combat this devastating pest. The discovery of PIP‐47Aa, along with several earlier examples (Sampson et al ., ; Schellenberger et al ., ; Yalpani et al ., ), indicates diverse bacteria other than Bt represent a potentially rich source for novel insecticidal proteins. Although the mechanism of insect toxicity of these newly discovered non‐ Bt proteins awaits further investigation, they share some characteristics with Bt proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the root node‐injury score is not as low as for corn producing Cry34Ab1/Cry35Ab1, PIP‐47Aa holds promise as a new tool to help combat this devastating pest. The discovery of PIP‐47Aa, along with several earlier examples (Sampson et al ., ; Schellenberger et al ., ; Yalpani et al ., ), indicates diverse bacteria other than Bt represent a potentially rich source for novel insecticidal proteins. Although the mechanism of insect toxicity of these newly discovered non‐ Bt proteins awaits further investigation, they share some characteristics with Bt proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, novel insecticidal proteins with activity against key crop insect pests have been identified from non-Bt microbes. These include a tiny insecticidal protein (Tip), IPD072Aa from P. chlororaphis (Schellenberger et al, 2016; Tabashnik, 2016), an insecticidal protein, GNIP1Aa, from Chromobacterium piscinae (Sampson et al, 2017), and a binary rootworm active AfIP-1A/1B, from Alcaligenes (Yalpani et al, 2017). Transgenic corn plants expressing IPD072Aa showed strong efficacy in glasshouse and field tests against WCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These novel toxins do not share receptors with Cry3A or Cry34/35Ab1 and neither showed cross-resistance in Cry3A-selected insects 10,11 , while IPD072Aa also showed no cross-resistance to Cry34/35Ab1-selected insects 10 . In addition a binary toxin named AflP-1A/1B isolated from the bacteria Alcaligenes faecalis was shown to be toxic against WCR although it shares a similar mode of action as the Cry34/35Ab1 toxin since WCR population resistant to Cry34/35Ab1 showed cross-resistance to AflP-1A/1B 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Biocontrol measures such as the use of Bacillus thuringiensis (Bt) pesticides or genetically modified plants that express insecticidal proteins are current alternative strategies. Bacteria such as Bt, B. popilliae , B. laterosporus, Alcaligenes faecalis , Pseudomonas chlororaphis , P. mosselii , and Paenibacillus lentimorbus have been reported to express insecticidal proteins and are toxic to coleopteran pests (Bravo, Likitvivatanavong, Gill, & Soberón, ; Höfte & Whiteley, ; Jouzani, Valijanian, & Sharafi, ; Sanchis, ; Schellenberger et al, ; Wei et al, ; Yalpani, Dan, & Barry, ; Yokoyama, Tanaka, & Hasegawa, ; Zhang, Hodgman, Krieger, Schnetter, & Schairer, ). In this review, we summarized these reported coleopteran‐pest‐specific bacteria and insecticidal proteins to provide a comprehensive overview and to offer long‐term guidance for the utilize of insecticidal proteins to control coleopteran pests in the future.…”
Section: Introductionmentioning
confidence: 99%